Impact of a hospice rapid response service on preferred place of death, and costs. Issue 1 (December 2015) - Gage, Heather; Holdsworth, Laura; Flannery, Caragh; Williams, Peter; Butler, Claire
Abstract Background Many people with a terminal illness would prefer to die at home. A new palliative rapid response service (RRS) provided by a large hospice provider in South East England was evaluated (2010) to provide evidence of impact on achieving preferred place of death and costs. The RRS was delivered by a team of trained health care assistants and available 24/7. The purpose of this study was to (i) compare the characteristics of RRS users and non-users, (ii) explore differences in the proportions of users and non-users dying in the place of their choice, (iii) monitor the whole system service utilisation of users and non-users, and compare costs. Methods All hospice patients who died with a preferred place of death recorded during an 18 month period were included. Data (demographic, preferences for place of death) were obtained from hospice records. Dying in preferred place was modelled using stepwise logistic regression analysis. Service use data (period between referral to hospice and death) were obtained from general practitioners, community providers, hospitals, social services, hospice, and costs calculated using validated national tariffs. Results Of 688 patients referred to the hospice when the RRS was operational, 247 (35.9 %) used it. Higher proportions of RRS users than non-users lived in their own homes with a co-resident carer (40.3 % vs. 23.7 %); more non-users lived alone or in residential care (58.8 % vs. 76.3 %). Chances of dying in the preferred place were enhanced 2.1 times by being a RRS user, compared to a non-user, and 1.5 times by having a co-resident carer, compared to living at home alone or in a care home. Total service costs did not differ between users and non-users, except when referred to hospice very close to death (users had higher costs). Conclusions Use of the RRS was associated with increased likelihood of dying in the preferred place. The RRS is cost neutral. Trial registration Current controlled trialsISRCTN32119670, 22 June 2012.